2001
DOI: 10.1159/000046038
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenomedullin Levels in Patients on Hemodialysis

Abstract: Adrenomedullin (AM) is a hypotensive peptide that has recently been isolated from human pheochromocytoma. In this study, we measured plasma AM concentrations in 54 patients on hemodialysis (HD) and examined the clinical significance. We also evaluated the effects of high-flux and low-flux dialysis membranes on plasma AM levels. The average value of plasma AM at pre-HD (4.44 ± 0.16 fmol/ml) was significantly elevated compared with that in 44 healthy volunteers (1.31 ± 1.41 fmol/ml) (p < 0.0001). The plasma AM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
(47 reference statements)
3
11
0
Order By: Relevance
“…Thus, plasma levels of PAMP, tAM and mAM seem to be positively related to increases in body fluid volume. Several studies have shown that plasma AM levels before HD are significantly higher as compared with controls [10, 11, 12, 13, 14, 15]. Mallamaci et al [12]reported that plasma AM falls after isolated ultrafiltration, indicating that the plasma concentration of this peptide is influenced by the status of the body fluid volume.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, plasma levels of PAMP, tAM and mAM seem to be positively related to increases in body fluid volume. Several studies have shown that plasma AM levels before HD are significantly higher as compared with controls [10, 11, 12, 13, 14, 15]. Mallamaci et al [12]reported that plasma AM falls after isolated ultrafiltration, indicating that the plasma concentration of this peptide is influenced by the status of the body fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…Protein clearance during HD varies with its molecular size and/or the type of dialysis membrane. In HD patients using cuprophan membranes (low-flux membrane), the plasma concentrations of tAM and mAM did not change during dialysis [10, 11, 14], whereas in patients using synthetic membranes (high-flux membrane), the plasma levels of these peptides decreased after HD [14, 15]. High-flux membranes are generally superior to low-flux ones in terms of removing low-molecular-mass proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations